2018
DOI: 10.4028/www.scientific.net/msf.920.46
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flange Length on the Distribution of Longitudinal Strain during the Flexible Roll Forming Process

Abstract: Flexible roll forming is an advanced sheet metal forming process which allows the production of variable cross-section profiles. In flexible roll forming process, nonuniform transversal distribution of the longitudinal strain can cause the longitudinal bow, which is deviation in height of the web over the length of the profile. To investigate the effect of flange length on the transversal distribution of the longitudinal strain, FEM simulations are conducted with different flange length for three blank shapes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…JOO et al [27] studied the flexible roll forming process of variable cross-section profiles and analyzed the effect of geometrical parameters such as base section width, side wall height and flange width on the longitudinal strain. Woo et al [28] used FEM simulation and experiment to study the influence of profile flange length on the transverse distribution of longitudinal strain in flexible roll forming, and the result showed that the longitudinal strain and longitudinal bow decrease with increasing flange length for a trapezoid and a concave blank. Abeyrathna et al [29] researched the effect of process and part shape parameters on the peak longitudinal edge strain, longitudinal bow and spring back for three different advanced high-strength steel (AHSS) and Ultra High Strength Steel (UHSS) commonly used in automotive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…JOO et al [27] studied the flexible roll forming process of variable cross-section profiles and analyzed the effect of geometrical parameters such as base section width, side wall height and flange width on the longitudinal strain. Woo et al [28] used FEM simulation and experiment to study the influence of profile flange length on the transverse distribution of longitudinal strain in flexible roll forming, and the result showed that the longitudinal strain and longitudinal bow decrease with increasing flange length for a trapezoid and a concave blank. Abeyrathna et al [29] researched the effect of process and part shape parameters on the peak longitudinal edge strain, longitudinal bow and spring back for three different advanced high-strength steel (AHSS) and Ultra High Strength Steel (UHSS) commonly used in automotive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Various models are available in the literature to predict the deformation for common shrink flanging or stretch flanging conditions [13] [12]. Previous work has revealed that common analytical models for shrink or stretch-flanging lead to a high deviation between the prediction and the experimental results for longitudinal strain in the flange [7][14] [15]. A recent study [16] has developed an advanced model to predict membrane/ longitudinal peak strains and strain distribution in a flexible roll-formed flange.…”
mentioning
confidence: 99%